Controle óptico e térmico das proopriedades ópticas e mecânicas de materiais fotônicos - Silva, Wagner Ferreira da (2011)
In this work we investigate how to control the optical and mechanical properties of photonic materials. Firstly we investigated the highly efficient 480 and 800 nm upconversion emissions from Tm3+/Yb3+ co-doped water-free low silica calcium aluminosilicate and tellurite glasses under resonant (976 nm) and anti-Stokes (1064 nm) excitations. As a result of these efficient upconversion processes, luminescent switches with the pump intensity and temperature (the latter under anti-Stokes excitation) have been observed. These switches were explained and discussed using rate equations analysis and saturation effects. Fitting the experimental data point provided the value of the energy transfer parameter related to the 2F5/2, 3H4->2F7/2, 1G4 transition. This switching mechanism could be used in the development of sensors and networks for optical processing and optical communications. Following the study of optical control of mechanical and optical proprieties, we investigated how to use femtosecond laser to write waveguides in Nd3+ doped YAG ceramics by multiple inscriptions of filaments, and if they are resistant to annealing temperatures. We studied two types of structures: “double-filament” and “square-filament” in Nd:YAG samples. We also reported, for the first time to our knowledge, on the fabrication of channel-buried optical waveguides in a Nd:YVO4 crystal by femtosecond laser inscription showing both TM and TE confinements. The optical waveguides obtained in this material emerge as promising candidates for highly efficient self-Raman integrated laser sources. And finalizing, we show the improvement of ultrafast laser written optical waveguides in Yb:YAG ceramics by tailoring the presence of heat accumulation effects. We showed how laser annealing can strongly reduce the concentration of defects and also reduce compressive estresse, leading to an effective 50% reduction in the propagation losses and to more extended and symmetric propagation modes. Micro-luminescence and micro-Raman imaging experiments have been carried out to elucidate the potential application of the obtained waveguides as integrated laser sources as well as to elucidate the waveguiding mechanisms.